Analysis Of The Effect Of Self-Efficiency, Position Promotion, And Work Environment On Employee Loyalty Through Job Satisfaction On Outsourcing Employees At PT Siemens Indonesia - Prihantoro, Dimas; Andriyanto, Wahyu Ari; Ariani, Nani (Universitas Pamulang, 2022)
This study was conducted to analyze the effect of self-efficacy, job promotion, and work environment on employee loyalty through job satisfaction on outsourced employees of PT. Siemens Indonesia. Companies must pay attention to employee self-efficacy, promotion opportunities, and the employee's work environment that can lead to employee job satisfaction. These things also have an important role in increasing employee loyalty. Several studies related to this writing have also been submitted by several authors, which resulted in a positive and significant influence between these variables. The research sample used is as many as 40 respondents outsourcing employees who work at PT. Siemens Indonesia. Analysis of the data in this study using PLS analysis using PLS software Version 3.0. The results showed that there was a positive but not significant effect between self-efficacy on job satisfaction, there was a positive and significant effect between job promotions on job satisfaction, there was a positive but not significant effect between work environment on job satisfaction, and there was a positive and significant effect. between job satisfaction and loyalty to outsourcing employees at PT. Siemens Indonesia.